INHIBITORY EFFECTS OF PLANT EXTRACTS ON MULTI-SPECIES DENTAL BIOFILM FORMATION IN-VITRO - NITHYA R.JOHN; VIRAJ C.GALA; CHHAYA S.SAWANT (International Journal of Pharma and Bio Sciences, 2013)
Dental biofilms play an important role in development of caries and periodontal disease, therefore their removal is integral to maintenance of oral hygiene. In the present study, different extracts prepared from Moringa oleifera, Murraya koenigii, Psidium guajava, Eclipta prostrata and Phyllanthus fraternus were screened for their effect on the growth, adherence and co-aggregation of a consortium of dental biofilm isolates. Results indicate, the test consortium was most susceptible to Ethanolic extract of M.koenigii and Aqueous–Ethanolic extracts of P.guajava and E.prostrata at their minimum inhibitory concentrations of 0.5 mg/ml, 1 mg/ml and 5 mg/ml respectively and effectively suppressed adherence and co-aggregation of test consortium at sub-MIC concentrations. Subsequently, aqueous–ethanolic extracts of P.guajava and E.prostrata demonstrated a log reduction of 3.5 and 4.2 log10cfu/ml respectively, in the viable count of dental biofilm load in-vitro. Hence, this study justifies the paradigm shift in oral care towards the use of nature-based products.